In vitro anti-cancer activity of hydro-ethanolic Urginea indica solution on human cervical HeLa, colon HT-29, and breast MCF-7 cancer cell lines - Sharad Maroti Porte; Anita Sharma (Wolters Kluwer Medknow Publications, 2023)
Introduction: Cancer is an abnormal uncontrolled growth of cells that can lead to death. Despite conventional therapies such as surgery, chemotherapy, radiotherapy, hormonal therapy and immunotherapy, cervical, breast, and colorectal cancer has been increased day by day. Hence, the Hydro-Ethanolic Solution of Urginea indica (Vanapalandu) bulb has taken for in vitro anticancer activity on cancer cell lines. Methods: The human cervical cancer cell HeLa, colon cancer cell HT-29, and breast cancer cell MCF-7 were grown and drugs were tested by the sulforhodamine B method. Results: The average value of the study drug was found 19.1, 22.5, 24.7, and 24.4, while the average value of adriamycin was found − 8.1, −34.4, −37.2, 6.6 in drug concentration of 10 μg/ml, 20 μg/ml, 40 μg/ml, 80 μg/ml, respectively, on cell line HeLa. The average value of the study drug has found were found 1.0, −27.3, −45.5, −52.3 while of adriamycin were found − 12.0, 2.7, 0.5,−3.8,−10.4 in concentrations 10 μg/ml, 20 μg/ml, 40 μg/ml, and 80 μg/ml, respectively, on cell Line HT-29. On cell line, MCF-7 the average value in the study drug was found 7.5, 4.5, 2.9,−8.2 while of adriamycin was found − 1.2, −21.4, −56.9, −53.1 in concentrations of 10 μg/ml, 20 μg/ml, 40 μg/ml, and 80 μg/ml, respectively. Conclusion: The anticancer activity of U. indica bulb extract was found more potential than adriamycin on the human colon cancer cell line.